Pengaruh Kunjungan Wisatawan, Industri Pariwisata Pada Penerimaan Pajak Hotel, Restoran Serta PAD di Wilayah SARBAGITA - Ibrahim, Muhammad Emil; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p20, 2022)
This study aims to analyze the effect of the number of tourist visits and the tourism industry on hotel restaurant tax receipts in the SARBAGITA Region, Bali Province. The data used is panel data for 2012-2019 with path analysis techniques. The results of the analysis show that the number of tourist visits has no effect on hotel and restaurant taxes; while the tourism industry has a positive effect. The number of tourist visits has no effect on PAD in the SARBAGITA area; the tourism industry and hotel and restaurant taxes have a significant positive effect on PAD in the SARBAGITA region of Bali Province. Hotel and restaurant taxes do not mediate the effect of the number of tourist visits on PAD in the SARBAGITA area of Bali Province. However, hotel and restaurant taxes mediate the influence of the tourism industry on PAD in the SARBAGITA area of Bali Province. Keywords: Tourist Visits; Tourism Industry; Hotel Restaurant Taxes; PAD.